NAA10 polyadenylation signal variants cause syndromic microphthalmia. Issue 7 (6th March 2019) - Johnston, Jennifer J; Williamson, Kathleen A; Chou, Christopher M; Sapp, Julie C; Ansari, Morad; Chapman, Heather M; Cooper, David N; Dabir, Tabib; Dudley, Jeffrey N; Holt, Richard J; Ragge, Nicola K; Schäffer, Alejandro A; et al.
Abstract : Background: A single variant in NAA10 (c.471+2T>A), the gene encoding N-acetyltransferase 10, has been associated with Lenz microphthalmia syndrome. In this study, we aimed to identify causative variants in families with syndromic X-linked microphthalmia. Methods: Three families, including 15 affected individuals with syndromic X-linked microphthalmia, underwent analyses including linkage analysis, exome sequencing and targeted gene sequencing. The consequences of two identified variants in NAA10 were evaluated using quantitative PCR and RNAseq. Results: Genetic linkage analysis in family 1 supported a candidate region on Xq27-q28, which included NAA10 . Exome sequencing identified a hemizygous NAA10 polyadenylation signal (PAS) variant, chrX:153, 195, 397T>C, c.*43A>G, which segregated with the disease. Targeted sequencing of affected males from families 2 and 3 identified distinct NAA10 PAS variants, chrX:g.153, 195, 401T>C, c.*39A>G and chrX:g.153, 195, 400T>C, c.*40A>G. All three variants were absent from gnomAD. Quantitative PCR and RNAseq showed reduced NAA10 mRNA levels and abnormal 3′ UTRs in affected individuals. Targeted sequencing of NAA10 in 376 additional affected individuals failed to identify variants in the PAS. Conclusion: These data show that PAS variants are the most common variant type in NAA10 -associated syndromic microphthalmia, suggesting reduced RNA is the molecular mechanism by which these alterations cause microphthalmia/anophthalmia. We reviewed recognised variants in PAS associated with Mendelian disorders and identified only 23 others, indicating that NAA10 harbours more than 10% of all known PAS variants. We hypothesise that PAS in other genes harbour unrecognised pathogenic variants associated with Mendelian disorders. The systematic interrogation of PAS could improve genetic testing yields.